Action of an endo-β-1,3(4)-glucanase on cellobiosyl unit structure in barley β-1,3:1,4-glucan - Kuge, Takao (Biosci Biotechnol Biochem, 2015)
β-1,3:1,4-Glucan is a major cell wall component accumulating in endosperm and young tissues in grasses. The mixed linkage glucan is a linear polysaccharide mainly consisting of cellotriosyl and cellotetraosyl units linked through single β-1,3-glucosidic linkages, but it also contains minor structures such as cellobiosyl units. In this study, we examined the action of an endo-β-1,3(4)-glucanase from Trichoderma sp. on a minor structure in barley β-1,3:1,4-glucan. To find the minor structure on which the endo-β-1,3(4)-glucanase acts, we prepared oligosaccharides from barley β-1,3:1,4-glucan by endo-β-1,4-glucanase digestion followed by purification by gel permeation and paper chromatography. The endo-β-1,3(4)-glucanase appeared to hydrolyze an oligosaccharide with degree of polymerization 5, designated C5-b. Based on matrix-assisted laser desorption/ionization (MALDI) time-of-flight (ToF)/ToF-mass spectrometry (MS)/MS analysis, C5-b was identified as β-Glc-1,3-β-Glc-1,4-β-Glc-1,3-β-Glc-1,4-Glc including a cellobiosyl unit. The results indicate that a type of endo-β-1,3(4)-glucanase acts on the cellobiosyl units of barley β-1,3:1,4-glucan in an endo-manner.